The Effect Of Entrepreneurship Education And Subjective Norms On Entrepreneurship Intentions Of Students Faculty Of Economics Class Of 2019 - Indah Sari, Putri; Marsofiyati, Marsofiyati; Purwana , Dedi (Jurnal Syntax Fusion, 2023)
This research is motivated by the low entrepreneurial intention among students of state universities in Jakarta. This study aims to determine the effect of entrepreneurship education and subjective norms on the entrepreneurial intentions of students of the Faculty of Economics, The State University of Jakarta, Class of 2019. This study uses a survey method with a questionnaire as a data collection instrument. The data collected was analyzed using tools in the statistical application program, namely Statistical Product and Service Solutions (SPSS). The population consisted of 160 students of the Faculty of Economics, State University of Jakarta, Class of 2019. This study found that entrepreneurship education had a positive and significant effect on entrepreneurial intentions, and subjective norms also had a positive and significant impact on entrepreneurial intentions of students of the Faculty of Economics, State University of Jakarta, Class of 2019.